The Impact of Personal Income Tax on Economic Growth: The Case of China and Thailand - Kaewsopa, Wanchai (Animo Repository, 2022)
This paper aims to study the impact of personal income tax (PIT) on economic growth in China and Thailand using the Chinese and Thai data, which were collected between 1999 and 2018, after the economic crisis of Thailand in 1997. The ordinary least squares (OLS) method was used to analyze the annual data for evaluating the impact of PIT on economic growth in the long run. The study revealed that in China, there is a significantly positive relationship between PIT and economic growth over the study period. On the other hand, Thailand’s PIT has a significantly negative relationship with economic growth. Corporate income taxes (CIT) in both China and Thailand have a negative impact on economic growth. Thailand’s value-added tax (VAT) has a negative relationship with economic growth, whereas VAT in China does not have a significant impact on economic growth. This study, therefore, recommends that the fiscal revenue policy used to stimulate economic growth should consider lowering CIT rather than PIT and VAT.